Constitutive Relationship for Hot Deformation of TB18 Titanium Alloy - Qiang Fu; Wuhua Yuan; Wei Xiang (Advances in Materials Science and Engineering)
In the present work, the hot deformation behavior of TB18 titanium alloy was investigated by isothermal hot compression tests with temperatures from 650 to 880°C and strain rates from 0.001 to 10 s−1. The flow curves after friction and temperature correction show that the peak stress decreased with the temperature increase and the strain rate decrease. Three typical characteristics of flow behavior indicate the dynamic softening behavior during hot deformation. At a strain rate of 0.001∼0.01 s−1, the flow stress continues to decrease as the strain rate increases after the flow stress reaches the peak stress; the flow softening mechanism is dynamic recovery and dynamic recrystallization at a lower temperature and dynamic recrystallization at a higher temperature. The discontinuous yielding phenomenon could be seen at a strain rate of 1 s−1, dynamic recrystallization took place in the β single-phase zone, and flow localization bands were observed in the α + β two-phase zone. At a higher strain rate of 10 s−1, the flow instabilities were referred to as the occurrence of flow localization by adiabatic heat. Constitutive equation considering the compensation of strain was also established, and the results show high accuracy to predict the flow stress with the correlation coefficient of 99.2% and the AARE of 6.1%, respectively.